Framing the household sustainable consumption and lifestyle in Malaysia: the policy implications - Zen, Irina Safitri; Ebrahimi, Mansoureh; Titisari, Prima Wahyu; Hendrayani, Yani (Hampstead Psychological Associates, 2020)
Given the plethora of choices and the abundance of products available in the market, household roles in practicing sustainable consumption and lifestyle in their daily life is crucial. As a newly industrialized country, Malaysian consumers are experiencing high consumerism spirits due to strong purchasing power. Hence, reoriented the complexities of consumption patterns towards sustainability requires defragmentation, prioritization and gradually change to find for more practical and strategic actions to overcome the barriers and policy intervention. Thus, this study aims to explore and analyze to what extend the sustainable consumption and lifestyle are being practices, ii. What are the barriers to foster the gradual changes to performs such behavior and iii.how the complexities of consumption structure to create the conducive environmental for behavioral changes towards sustainable behaviour. The study found the contextual factors of availability green products and barriers need to overcome as to develop the household sustainable lifestyle. Most of the household sustainable lifestyle practices and purchase are driven by the economic rationalities rather than environmental reasons. The complexities of interrelated of consumption are structured into an integrative framework of household sustainable lifestyle and consumption which recognized the contextual factors sustainable purchase and barriers to strengthen the sustainable behavior. From this study, four points of policy interventions level are recognized to overcome the barriers in performing sustainable lifestyle and consumption. The four are product innovation, technical innovation, governance approaches and knowledge, awareness and advocacy. Various policy instruments related to sustainable lifestyle and consumption are proposed by considering the contextual factor of sustainable consumption and lifestyle in Malaysia.